Makna Kepercayaan pada Perempuan Lajang yang Pernah Mengalami Perselingkuhan - Nailatul Khairiyah A; Naya Salim Hijria; Nurul Indah Nia; Nayla Putri Hendrina; Maesya Kahira; Fahira Inayah Syazwani; Sintia Anugra Ananda; Agitia Kurniati Asrila (Batanang : Jurnal Psikologi, 2026)
Interpersonal trust in romantic relationships is an important issue to examine, particularly because experiences of betrayal such as infidelity can have a significant impact on how individuals form and maintain relationships in the future. For single women, such experiences not only affect their emotional readiness but also reshape their patterns of trust when entering new relationships. However, to date, our understanding of how individuals interpret trust after experiencing betrayal remains limited. Therefore, this study aims to explore the meaning of interpersonal trust among single women who have experienced infidelity in a romantic relationship. This study employs a phenomenological qualitative approach using Interpretative Phenomenological Analysis (IPA) to explore the participants’ subjective experiences in greater depth. The participants consisted of three single women selected through purposive sampling, and data were collected through in-depth interviews. The research findings reveal three main themes: the dynamics of infidelity, readiness for a relationship, and efforts to build self-confidence. Experiences with infidelity have been found to influence interpersonal trust, particularly in terms of reliability, emotional support, and honesty. In response, participants developed self-protection mechanisms by increasing their vigilance and limiting their emotional involvement in relationships. Nevertheless, these experiences did not completely erode interpersonal trust. Through a process of self-reflection and acceptance of their experiences, participants were gradually able to restore and rebuild trust in their relationships.